2013
DOI: 10.3122/jabfm.2013.01.120051
|View full text |Cite
|
Sign up to set email alerts
|

Do Older People Benefit from Having a Confidant? An Oklahoma Physicians Resource/Research Network (OKPRN) Study

Abstract: Objective:The objective was to determine whether having a confidant was associated with improved health-related quality of life (HRQoL) or survival in older, community-dwelling individuals.Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
15
1
Order By: Relevance
“…Subsequent publications often reported effect estimates over different lengths of follow-up or using different QoL tools. Two published articles of De Buyser et al reported the results of the same populationbased cohort study [41,42], three published articles by De Salvo et al and Fan et al were from the same study and included participants enrolled in the Veterans Affairs Ambulatory Care Quality Improvement Project [24,43,47], two published studies of Mold et al and Lawler et al used the same communitydwelling cohort [57,61], two published studies of Higueras-Fresnillo et al and Otero-Rodriguez et al were from the same Spanish cohort [52,67], two published studies of Feeny et al and Kaplan et al were from the same Canadian cohort [48,55]; and Myint et al published three articles [26,64,65] with different perspectives on the same population-based study. Additionally, Liira et al's study [29], included eight individual cohorts, however, only ve of the cohorts met the inclusion criteria for this current systematic review, and thus are shown in Table 1.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent publications often reported effect estimates over different lengths of follow-up or using different QoL tools. Two published articles of De Buyser et al reported the results of the same populationbased cohort study [41,42], three published articles by De Salvo et al and Fan et al were from the same study and included participants enrolled in the Veterans Affairs Ambulatory Care Quality Improvement Project [24,43,47], two published studies of Mold et al and Lawler et al used the same communitydwelling cohort [57,61], two published studies of Higueras-Fresnillo et al and Otero-Rodriguez et al were from the same Spanish cohort [52,67], two published studies of Feeny et al and Kaplan et al were from the same Canadian cohort [48,55]; and Myint et al published three articles [26,64,65] with different perspectives on the same population-based study. Additionally, Liira et al's study [29], included eight individual cohorts, however, only ve of the cohorts met the inclusion criteria for this current systematic review, and thus are shown in Table 1.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Among the 23 studies which examined mental HRQoL (one exclusively assessed MCS), 13 studies (57%) reported that higher mental HRQoL was associated with decreased mortality risk ( Table 1). The ve studies [49,52,57,59,76] that measured HRQoL using SF-36 or SF-20 reported not only the physical functioning and mental health domains, but also general health perception, bodily pain, vitality, and social functioning. The ndings were generally consistent in general health perception and social functioning; and it was reported that better level of general health perception and social functioning was associated with decreased mortality risk ( Table 1).…”
Section: Qualitative Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 23 studies which examined mental HRQoL (one exclusively assessed MCS), 13 studies (57%) reported that higher mental HRQoL was associated with decreased mortality risk ( Table 1). The ve studies [49,52,57,59,76] that measured HRQoL using SF-36 or SF-20…”
Section: Qualitative Synthesismentioning
confidence: 99%
“…Six studies including 22,570 participants [42,46,57,59,68,76] measured QoL using the SF-36 and investigated the association between the physical functioning and all-cause mortality using time-to-event survival analysis. With an average 8.7-year follow-up, one unit increase in the SF-36 PF was associated with a 1.3% decrease in time to death (pooled HR = 0.987; 95%CI: 0.982 to 0.992; P-value < 0.001).…”
Section: Qualitative Synthesismentioning
confidence: 99%